(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
In the article, the coordination compound formed by cobalt (II)- nitrate hexahydrate, quinazolin-4-one and indole fatty acids is used for the production of cotton "Sultan", "Unkurgon-1" varieties for the first time we want to present the processes of influence on the rooting system. Until now, synthesis processes and biological effects have been studied by individuals, and coordination compounds with these substances have not been synthesized.